Power, Knowledge and Feminist Scholarship: An Ethnography of Academia - do Mar Pereira, Maria (Transformations, 2017)
Feminist scholarship is sometimes dismissed as not quite ‘proper’ knowledge – it’s too political or subjective, many argue. But what are the boundaries of ‘proper’ knowledge? Who defines them, and how are they changing? How do feminists negotiate them? And how does this boundary-work affect women’s and gender studies, and its scholars’ and students’ lives? These are the questions tackled by this ground-breaking ethnography of academia inspired by feminist epistemology, Foucault, and science and technology studies. Drawing on data collected over a decade in Portugal and the UK, US and Scandinavia, this title explores different spaces of academic work and sociability, considering both official discourse and ‘corridor talk’. It links epistemic negotiations to the shifting political economy of academic labour, and situates the smallest (but fiercest) departmental negotiations within global relations of unequal academic exchange. Through these links, this timely volume also raises urgent questions about the current state and status of gender studies and the mood of contemporary academia. Indeed, its sobering, yet uplifting, discussion of that mood offers fresh insight into what it means to produce feminist work within neoliberal cultures of academic performativity, demanding increasing productivity. As the first book to analyse how academics talk (publicly or in off-the-record humour) about feminist scholarship, Power, Knowledge and Feminist Scholarship is essential reading for scholars and students in gender studies, LGBTQ studies, post-colonial studies, STS, sociology and education. Winner of the FWSA 2018 Book Prize competition The Open Access version of this book, available at https://doi.org/10.4324/9781315692623, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.